IMPLEMENTACIÓN CONTABLE EN EL COMERCIAL “PLAZA CENTRO” DE LA PARROQUIA VILCABAMBA, PERÍODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2020 - Ordóñez Márquez, Carla Daniela (2021)
The present thesis titled “ACCOUNTING IMPLEMENTATION IN THE COMMERCIAL “PLAZA CENTRO” OF THE VILCABAMBA TOWN, PERIOD FROM SEPTEMBER 01 TO DECEMBER 31, 2020, has the main objective of implementing the appropriate commercial accounting for the company, so that it will allows the owner, Mr. Juan Carlos Ordoñez Bejarano, to obtain the necessary information about the commercial's economic and financial situation for correct decision-making. To comply with the proposed objectives, it was necessary to apply techniques and methods to obtain the information that would allow a plan and manual of accounts to be made according to the nature of the comercial. The accounting process began with the control of the initial inventory where all the goods, rights and obligations that the owner have at the beginning of his activities are detailed, the documentation provided by the owner helped in the elaboration of the plan and the accounts manual, as well as in the realization of the memorandum of operations, to later open the journal and ledgers, which allowed preparing the trial balance, worksheet, adjustments and at last the Financial Statements. Finally, it was obtained as a result the accounting implementation in the commercial “Plaza Centro” which allowsto have clear, orderly and timely information; as well as a better organization and control of its commercial operation, that is the reason why its owner is recommend to accept this investigative work, as a tool that allows him to know the economic and financial situation in a determinate period, thus facilitating correct decision-making.